Adaptation Policy Frameworks for Climate Change:Developing Strategies, Policies and Measures - Lim, Bo; Spanger-Siegfried, Erika (editors) (Cambridge : Cambridge University Press, 2005)
Environment Management
2007\08\01
Keywords: Climate; Climatic Changes; Climatology